If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + (-12y) + (-15x) + 9y = 0 Reorder the terms: 11x + (-15x) + (-12y) + 9y = 0 Combine like terms: 11x + (-15x) = -4x -4x + (-12y) + 9y = 0 Combine like terms: (-12y) + 9y = -3y -4x + -3y = 0 Solving -4x + -3y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3y' to each side of the equation. -4x + -3y + 3y = 0 + 3y Combine like terms: -3y + 3y = 0 -4x + 0 = 0 + 3y -4x = 0 + 3y Remove the zero: -4x = 3y Divide each side by '-4'. x = -0.75y Simplifying x = -0.75y
| 2x-1y=-30 | | Q=75-p | | 5.7q-5.2-5.3q=-0.6q-4.5 | | 3x+25-30x=16 | | -a-3a=7(4a-3)+4(6-8a) | | x+2x+(x+10)=166 | | 3(3+x)=17+x | | 16v^2-8v+1= | | 6s-20=4+8s | | y=10+-4x | | 4x+2x=108 | | y+2/8=y-2/7 | | x^6*x= | | x+2x+(x+17)=129 | | 3s-17=-7+5s | | x/4+4/7 | | -5(x+11)+365=19+16 | | 3x+3=17+x | | 2x+2x=100 | | 3t-15=60+8t | | 7p/5+p=12 | | log^2(x^2-6x-23)=2 | | (w^2+w-20)(w^2+11w+30)3+(w^2+2w-24)(w^2+11w+30)1=(w^2+2w-24)(w^2+w-20)3 | | 4x^2+29x-30=0 | | (w^2+w-20)(w^2+11w+30)3+(w^2+2w+24)(w^2+11w+30)1=(w^2+2w-24)(w^2+w-20)3 | | 2-3(2x-1)=2 | | 5(3+4x)-2=33 | | 8x-3=11+6x | | 3x+7(4x-12)=133 | | 3x+3x=144 | | 2v^2+3=-7v | | y^2+18xy+81x^2= |